Analisis Kelayakan Finansial Usaha Gula Kelapa (Studi Kasus pada PO Sumber Agung, Desa Surya Mataram) - Bambang Suhada; Fitriani; Erlita Pramisella (Universitas Muhammadiyah Metro, 2025)
A business certainly has the aim of continuing to develop and be able to compete with competitors and it is necessary to carry out a business/enterprise feasibility study with the aim of minimizing obstacles and risks that may arise in the future or in the future. Whether a business is viable or not will have a main goal, namely obtaining optimal profits. This research was conducted to determine whether PO Sumber Agung's coconut sugar business is financially viable to continue the business or not. This research used qualitative research using financial analysis such as NPV, IRR, Payback Period (PP), Net B/C Ratio, BEP with research instruments in the form of documentation and interviews. The sample in this research used 35 coconut sugar farmers. The results of the analysis show that the results of financial feasibility with 100% own capital are declared feasible with an NPV is positive (+) 54, 855, 574; This figure is > 0 which indicates the financial feasibility of the business, the IRR value is 37.9%, the Net B/C Ratio is 5.416 or > 1, the payback period is 8 months 25 days. where the NPV is positive, the Net B/C is greater than one and the IRR is greater, then from a financial perspective this business is worth pursuing.